The influence of parenting classes on maternal self-efficacy in caring for the baby - Elin Supliyani; Ina Handayani; Suhartika Suhartika; Dedes Fitria (PAGEPress Publications, 2024)
Preparing for childbirth is crucial because it was a demanding and exhausting experience for unprepared mothers. Confidence in caring for the baby was one of the important indicators of success as a parent. This study aimed to examine the influence of parenting classes on maternal self-efficacy in caring for the baby. The study used a quasi-experimental pre-test and post-test nonequivalent control group design method. The research was conducted at several Midwife Clinical Practices in Bogor City. The sample consisted of 42 pregnant women, with 21 in the intervention group and 21 in the control group. Sampling used non-probability sampling with a purposive sampling technique. The Perceived Maternal Parenting Self-Efficacy (PMP-SE) questionnaire with a likert scale was used to measure the mother's self-efficacy variable in caring for the baby before and after attending the parenting class. The data were analyzed using the Wilcoxon test. The results showed that the mean self-efficacy of mothers in caring for their babies before the intervention was 42.57 (8.577), and after attending the parenting class, it increased to 47.71 (8.344). There was a significant influence of parenting class on mothering self-efficacy in caring for the baby (p=0.015). It is recommended that this model of parenting classes be applied in healthcare settings to educate pregnant women on readiness to become parents, thereby increasing mothers' confidence and ability to take care of their babies after childbirth.